Clima organizacional en la asociación CORPICSUPAL Dedicados A La Producción De Plátano Barraganete (Musa AAB) - Ruedas Loor, Evelyn Estefanía (2023)
The research focused on determining the organizational climate within Corpicsupal, an association dedicated to the production of barraganete bananas (Musa AAB), and how it influences the organizational commitment of its members. The achievement of the objectives set out was carried out using an analytical approach, which allowed for the identification of the prevailing organizational climate in the association. The synthetic method was also utilized, through which the main findings related to the organizational climate in Corpicsupal were compiled and summarized. Various techniques such as interviews, surveys, and correlation analysis were employed to collect relevant information. The study included all 68 active members of Corpicsupal, each responsible for their own production units, or agribusinesses. The research revealed an effective organizational structure and solid administrative processes within the association. Members expressed a high level of satisfaction and commitment towards Corpicsupal, although a need for more support for their personal growth was identified. Highlighted elements included direct communication with the owners and a productivity-based reward system. The conclusion derived from the study indicates that there is no significant correlation between the dimensions of the organizational climate and the organizational commitment within Corpicsupal.